Pengaruh Modal, Jam Kerja, Lama Usaha dan Religiusitas terhadap Pendapatan Pedagang Sate Madura di Kota Jambi - Retno Bulan Salsabilah; Agustina Mutia; Ahmad Syahrizal (Pusat Riset dan Inovasi Nasional, 2025)
Income is the main component for everyone in this world, income or income influences business continuity. The capacity of a business to support movement of any type that helps maintain the business significantly impacts how much payment the business gets. The aim of this research aims to find out how partially and partially Capital, Working Hours, Length of Business and Religiosity affect the Income of Madura Sate Traders in Jambi City. In this research, researchers used the Quantitative Descriptive method. The sample used in this research was 32 respondents from Madurese Satay traders in Jambi City. To collect data using questionnaires, interviews and documentation. The analysis techniques used are Data Quality Test, Classic Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis and Coefficient of Determination. The research results show that: Capital (X1) has a significant effect on income. Working Hours (X2) has a significant effect on Income. Length of Business (X3) has a significant effect on Income. Religiosity (X4) has a significant effect on income. Capital (X1), working hours (X2), length of business (X3) and religiosity (X4) simultaneously have a significant effect on the income of Madurese satay traders in Jambi City (Y).